(untitled) (Journal of the Bangladesh Chemical Society, 2013)
Dissipation pattern of cypermethrin (Ripcord 10EC) on tomato plants sprayed at recommended and double the recommended doses followed first order kinetics. In both the doses residues were found below the maximum residue level (0.5 ppm) after one day of application. Recoveries were found to be 80.88% &77.09% spiked at 0.2 & 0.5 ppm, respectively. LOD and LOQ were found to be 0.01 and 0.06 ppm, respectively. Journal of Bangladesh Chemical Society, Vol. 25(2), 200-203, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15087